Copy number variations of neurotrophic tyrosine receptor kinase 3 (NTRK3) may predict prognosis of ovarian cancer. Issue 30 (July 2017) - Ge, Li; Li, Ning; Liu, Mei; Xu, Ning-Zhi; Wang, Ming-Rong; Wu, Ling-Ying
Abstract : Abstract: Platinum resistance is a critical barrier for clinicians to improve the survival of ovarian cancer. Our study evaluated the correlation between copy number variations (CNVs) of neurotrophic tyrosine receptor kinase 3 (NTRK3) and the prognosis of ovarian cancer, which might predict platinum resistance in ovarian cancer patients. Array comparative genomic hybridization (CGH) was used to test gene backgrounds between platinum-sensitive and platinum-resistant relapsed populations and CNVs of NTRK3 were indicated by cluster analysis. Fluorescence in situ hybridization (FISH) was adopted in 41 cases for further verification, which confirmed the results of array CGH. Spearman's rank correlation analysis and χ 2 test were used to evaluate the accuracy of CNVs of NTRK3 which predicted platinum-sensitive or platinum-resistant recurrence. We detected CNVs of NTRK3 between 2 groups by array CGH, and amplification of NTRK3 was confirmed by FISH in the platinum-sensitive recurrence group with enlarged samples. The test concordance of 2 methods was 78.6%. Among 41 cases with satisfied FISH results, the median time to recurrence (TTR) of patients with amplified and nonamplified NTRK3 were respectively 18 and 5 months ( P <.01). The cut-off value of TTR to differentiate platinum-sensitive or platinum-resistant recurrence was 6 months in accordance with clinical practice. According to the above standard, 15 cases with NTRK3 amplification were platinum-sensitive and 12 cases without NTRK3 amplification were platinum-resistant recurrences which demonstrated that the accuracy of NTRK3 amplification/nonamplification to predict recurrent types was 65.9% (27/41). CNVs of NTRK3 were associated with platinum-sensitive and platinum-resistant recurrences. Amplification of NTRK3 perfectly predicted platinum-sensitive relapse of ovarian cancer.